Clinical profile, etiology and histopathology of patients with erythroderma in South India - O., Snigdha; George, Mamatha; M. P., Binitha; Balakrishnan, Sunitha (International Journal of Research in Dermatology, 2017)
Background: Erythroderma is a generalised inflammatory disorder of skin manifesting with erythema and scaling affecting more than 90% of the skin surface. Several studies have highlighted the importance of biopsy in the diagnosis and management of erythroderma, while some others have found it to be of limited use. Methods: Thirty-six patients with erythroderma were enrolled in the study and a detailed history, clinical examination and relevant investigations including skin biopsy was done to find out the etiology. Results: Pre-existing dermatoses were the predominant cause (84%) contributed equally by psoriasis (42%) and eczemas (42%) and clinicopathologic correlation could be obtained in 30.55% of cases. Conclusions: Our study showed that skin biopsy remains a valuable tool in the diagnosis of erythroderma.